Effect of Sling Neck Flexion Exercise on Concentration and Brain Activity of Subjec ts with Forward Head Posture - Bae, Won-Sik; Lee, Dong-Yeop; Lee, Keon-Cheol (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to investigate the effect of sling neck flexion exercise o n attention and brain activity in subjects with forward head posture (FHP).Method/statistical Analysis: The study group comprised 30 students who were randomly divided into two grou ps. One group(15 students) took part in sling neck flexion exercise for 6 wk, and the other group(15 students) se rved as the control. FHP was determined using a global postural system (GPS 400) device. An electroencephalo gram (EEG) was performed using EEG 3000 to assess left and right brain activity.Findings: A homogeneity test revealed that the general characteristics of the subjects in the two groups did not significantly differ. A paired t-test and independent t-test were performed to analyze differences between and within two groups. The change in concentration according to the experiment duration showed a significant difference in the experimental group (p.05). While the change in the left brain activity showed a significant difference in the experimental group (p.05). The mean at each time period showed no significant difference between the two groups (p>.05). While the experimental group showed a significant difference in the change in the right brain activity according to the experiment duration (p.05). The between-group difference of the mean at each time period showed no significance (p>.05).Improvements/Applications: In conclusion, sling neck flexion exercise can improve brain function. Regular po stural correction exercise is required. We expect the results to be used in clinical trials.